Symptom burden and post-COVID-19 syndrome 24 months following SARS-CoV-2 infection: Longitudinal population-based study - Peter, Raphael Simon; Sedelmaier, Lisamaria; Nieters, Alexandra; Brockmann, Stefan O.; Göpel, Siri; Merle, Uta; Steinacker, Jürgen M.; Kräusslich, Hans-Georg; Rothenbacher, Dietrich; Kern, Winfried V. (Journal of infection, 2025)
Objectives - To describe the symptom burden and associated impairment two years after SARS-CoV-2 index infection. - Methods - Participants of an earlier large population-based survey in Southwestern Germany (August-September 2021) were contacted again in November 2023. We calculated the prevalences of suspected PCS and specific symptom clusters at both time points and investigated factors for their resolution or emergence. - Results - A total of 6635 subjects (mean age 46.6 years, 60.9% females) participated in the follow-up. Between baseline and follow-up (median 8.7 and 23.9 months after infection) there were only small changes in the point prevalence of post-COVID-19 syndrome (PCS) (29.9% versus 31.2%) or defined symptom clusters such as fatigue (23.8% versus 22.0%), neurocognitive impairment (15.8% versus 17.3%), or chest symptoms (14.4% versus 13.7%). Probabilities of resolution were often similar to probabilities of emergence, e.g. fatigue symptoms resolved in 9.8% of participants but emerged in 8.0%. Consistent predictors for emerging symptom clusters were female sex, obesity and medical treatment of the acute infection. The six main symptom clusters together explained 45% (physical domain) and 29% (mental domain) of the variance in health-related quality of life (hrQoL). - Conclusions - We found a remaining high symptom prevalence two years after SARS-CoV-2 infection, but symptoms present nine months after the index infection often resolved, which was associated with increasing hrQoL. Remarkably, a considerable portion of symptoms newly emerged, of which only a few could be attributed to reported SARS-CoV-2 reinfection.
Gesehen am 29.10.2025